Thermal sensation and thermal comfort in changing environments. (March 2017) - Velt, K.B.; Daanen, H.A.M.
Abstract: It is the purpose of this study to investigate thermal sensation (TS) and thermal comfort (TC) in changing environments. Therefore, 10 subjects stayed in a 30 °C, 50% relative humidity for 30 min in summer clothes and then moved to a 20 °C room where they remained seated for 30 min (Hot to Reference - HR). Similarly, 11 subjects moved from a 10 °C, 50% relative humidity to a 20 °C environment (Cold to Reference – CR) dressed in winter garments. TS (9 point scale from −4 (very cold) to +4 (very hot)) decreased from 1.5±0.4 (mean±SD) to −0.8±0.8 for HR and increased from −1.7±1.4 to 0.8±0.9 for CR. TC (5 point scale from 0 (comfortable) to +4 (extremely uncomfortable)) dropped from 1.5±0.5 to 1.2±0.4 for HR and from 1.9±0.7 to 1.3±0.4 for CR. The difference in TS between HR and CR at the end of period in 20 °C illustrates the considerable dependence of thermal sensation on exposure history. It is therefore recommended to increase room temperature when it is hot outside and decrease room temperature when it is cold outside in order to maintain a neutral thermal sensation. Highlights: Thermal sensation and comfort are dependent on exposure history. Rooms should be relatively cold in winter and warm in summer for thermoneutral feeling. Core temperature paradoxically drops when moving from cold to a 20 °C room. Humans are NOT more sensitive to temperature declines than to temperature increases.